Examination of temporomandibular disorders in the orthodontic patient: a clinical guide - Ana Claúdia de Castro Ferreira Conti; Paula Vanessa Pedron Oltramari; Ricardo de Lima Navarro; Márcio Rodrigues de Almeida (University of São Paulo, 2007)
The possible association between orthodontic treatment and temporomandibular disorders (TMD) is a topic of great interest in the current literature. The true role of orthodontic therapy on the etiology of TMD, however, is still uncertain. From the clinical prospective, a thorough examination of the stomatognathic system is always necessary in order to detect possible TMD signs and symptoms prior to the beginning of the orthodontic therapy. Caution should be exercised when planning, performing and finalizing orthodontics, especially in patients who with history of signs and symptoms of TMD. The clinician must always eliminate patient's pain and dysfunction before initiating any type of orthodontic mechanics. Muscle incoordination, unstable disc-condyle relationship and bone alterations are usual TMD conditions that can interfere with the presenting occlusal relationship. This article reviews these aspects and presents a detailed clinical guide for the examination of the orthodontic patient, considering aspects related to facial pain and dysfunction.